2020
DOI: 10.14260/jemds/2020/133
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Study of Urine Albumin Creatinine Ratio as an Earlier Predictor of Diabetic Nephropathy

Abstract: A B S T R A C T BACKGROUNDDiabetic nephropathy (DN) is a chronic microvascular complication of diabetes mellitus (DM). Microalbuminuria is an earliest marker of DN. Effective screening measures are required for early diagnosis and management to halt the progression of diabetic nephropathy. We wanted to evaluate urine Albumin Creatinine Ratio (ACR) as an earlier predictor of diabetic nephropathy in comparison to the gold standard test 24-hours urine protein. METHODSThis is a cross sectional study conducted amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 16 publications
0
0
0
4
Order By: Relevance
“…Besides, the data of the present trial demonstrated an increase in the albumin to creatinine ratio (ACR) in urine with longer durations of diabetic nephropathy. These results are consistent with some studies [59], also with [60], who concluded that the duration of diabetes and advanced age could help predict the development of complications of diabetic kidney disease and deaths. The result probably due to the structural and functional changes of the body systems in people over the age of 60 years, in addition to the damage that occurs because of long duration diabetes, causing albuminuria, which is considered one of the important diagnostic criteria [61].…”
Section: Discussionsupporting
confidence: 93%
“…Besides, the data of the present trial demonstrated an increase in the albumin to creatinine ratio (ACR) in urine with longer durations of diabetic nephropathy. These results are consistent with some studies [59], also with [60], who concluded that the duration of diabetes and advanced age could help predict the development of complications of diabetic kidney disease and deaths. The result probably due to the structural and functional changes of the body systems in people over the age of 60 years, in addition to the damage that occurs because of long duration diabetes, causing albuminuria, which is considered one of the important diagnostic criteria [61].…”
Section: Discussionsupporting
confidence: 93%
“…При хронічній гіперглікемії відбувається активація перекисного окиснення ліпідів, підвищення секреції цитокінів і активація проліферації клітин [13]. Встановлено, що рівень глікозильованого гемоглобіну (HbA1C) є незалежним ФР мікроальбумінурії (МАУ) [14]. Тому на любих стадіях ДН необхідно прагнути досягнення індивідуального цільового рівня HbA1C в межах від 6,5 % до 7,0 %, що дозволяє знизити ризик виникнення і прогресування ДН при обох типах ЦД.…”
Section: гіперглікеміяunclassified
“…При останній відбувається згладжування ніжок подоцитів з порушенням проникності щілинної діафрагми, гіпертрофія, апоптоз, відшарування подоцитів від базальної мембрани клубочків зі злускуванням їх в сечовий простір і появою в сечі як цілих клітин (подоцитурія), так і їх структурних білків (нефрину, подоцину та ін.) [4,14]. Паралельно спостерігається зменшення кількості подоцитів в клубочці -подоцитопенія.…”
Section: порушення метаболізму ліпідівunclassified
See 2 more Smart Citations